Changes in interferon-γ release assay readout after COVID-19 vaccination: A prospective cohort study. (September 2022) - Chen, Nan-Yu; Liu, Zhuo-Hao; Kao, Shu-Wei; Lin, Huang-Shen; Lee, Ing-Kit; Zheng, Jun-Yuan; Wang, Ssu-Wei; Hsiao, Yu-Hsiang; Lin, Hui-Chin; Wu, Ting-Shu
Highlights: l COVID-19 vaccines impact interferon-γ release assay readouts l COVID-19 vaccines significantly change the Nil and Mitogen-Nil values l COVID-19 vaccines did not change interferon-γ release assay interpretation in most cases Abstract: Objectives: Interferon-γ release assays (IGRAs) are widely used in public health practice to diagnose latent tuberculosis. During the COVID-19 pandemic and rollout of COVID-19 vaccination, it has remained unclear whether COVID-19 vaccines interfere with IGRA readouts. Methods: We prospectively recruited healthcare workers during their annual occupational health examinations in 2021. Baseline IGRA readouts were compared with follow-up data after the participants had received two doses of COVID-19 vaccination. Results: A total of 134 baseline IGRA-negative cases (92 with ChAdOx1 vaccine, 27 with mRNA-1273 vaccine, and 15 with heterologous vaccination) and seven baseline IGRA-positive cases were analyzed. Among the baseline IGRA-negative cases, there were decreased interferon-γ concentrations over the Nil ( P = 0.005) and increased Mitogen-Nil ( P < 0.001) values after vaccination. For TB2-Nil value, a similar trend ( P = 0.057) of increase was observed. Compared with the 0.35 IU/ml threshold, the baseline and follow-up readout differences were less than |± 0.10| IU/ml over the TB1-Nil and TB2-Nil values in >90% baseline IGRA-negative cases. No significant readout difference was observed among baseline IGRA-positive cases. Conclusion: COVID-19 vaccination did not change IGRA interpretation in most cases. Cases showing conversion/borderline IGRA readouts should be given special consideration.